The Influence of Promotion, Trust and Customer Experience on Customer Loyalty through Customer Satisfaction at LPK “Maju Jaya” in Grobogan - Rahayu, Sucik; Hwihanus, Hwihanus (Sharia Economics Department Universitas KH. Abdul Chalim, Mojokerto, 2024)
The objective of this study is to demonstrate and evaluate the effects of customer satisfaction at LPK